Perancangan Animasi 2D Warisan Budaya Senjata Tradisional Kerambit - Muhammad Hanif Syofwan; Eko Purnomo (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
Teenagers, especially in West Sumatra, do not know about kerambit as a traditional weapon originating from West Sumatra. Even though the kerambit itself was used by the US army as a military weapon, its origins were not really known by the West Sumatran teenagers themselves. This is the result of teenagers' lack of curiosity about history and a lack of media that can attract their attention. The aim of designing this 2D animation is to foster teenagers' interest in studying history with new media and provide education about kerambit and its history through 2D animation media by utilizing social media as promotional media. The method used in this design is the 4D method, which consists of define, design, develop and disseminate. Using the 5W+1H data analysis method. This design produces main media in the form of 2D animated videos, and supporting media in the form of t-shirts, printed posters, stickers, social media content, Acrylic stands, and x-banners.